Motivasi Mahasiswa dalam Berorganisasi di Pergerakan Mahasiswa Islam Indonesia (PMII) - Mukarromah, Al; Rosda, Ariena Billahi (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
This research discusses the motivation of students in organizing in PMII Commissariat Kebayoran Lama. Motivation gives encouragement and hope to students to achieve their goals. This study aims to explore and describe student motivation in organizing at PMII Commissariat Kebayoran Lama for Mapaba members in 2022. The method used in this research is a descriptive qualitative approach, using Abraham Maslow's motivation theory or familiarly called the hierarchical theory of basic human needs. The data collection techniques used were online written interviews via Google Form, literature study and non-participant observation. The results showed that the motives that form student motivation in organizing in PMII Commissariat Kebayoran Lama are because Mapaba is an effective cadre forum, PMII Commissariat Kebayoran Lama as a forum for self-actualization to support future careers, having an extensive network of relationships, PMII as an organization born from the womb of Nahdlatul Ulama, and following the advice of the closest people. In Abraham Maslow's theory of motivation, it is found that the motivation of students is to meet the need for security to want to organize comfortably and safely according to the advice of those closest to them. Social needs to have different friends in order to build extensive relationships. Appreciation needs, students want to get the appreciation of being someone who succeeds in society. Finally, self-actualization needs, students want to develop their interests talents and passions to improve their quality of life in achieving their future careers.